2020
DOI: 10.1021/acsomega.0c01256
|View full text |Cite
|
Sign up to set email alerts
|

β-Carboline Derivatives Tackling Malaria: Biological Evaluation and Docking Analysis

Abstract: Increasing resistance to presently available antimalarial drugs urges the need to look for new promising compounds. The β-carboline moiety, present in several biologically active natural products and drugs, is an important scaffold for antimalarial drug discovery. The present study explores the antimalarial activity of a β-carboline derivative (1 R ,3 S )-methyl 1-(benzo[ d ][1,3]dioxol-5-yl)-2,3,4,9-tetrahydro-1 H -pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…To study various aspects of mammalian malaria, such as developmental biology, interactions between the parasite and its host, development of vaccines, and testing of novel drug candidates, rodent-infecting Plasmodium species are recognized as valuable experimental models as they have a conserved genome organization, basic biology, housekeeping genes and biochemical processes, as well as characteristic patterns of drug sensitivity and resistance that are similar to human-infecting species of Plasmodium . 22 23 Hence, P. berghei (NK-65) is the experimental model used for carrying out drug screening assays because P. falciparum cannot be maintained in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…To study various aspects of mammalian malaria, such as developmental biology, interactions between the parasite and its host, development of vaccines, and testing of novel drug candidates, rodent-infecting Plasmodium species are recognized as valuable experimental models as they have a conserved genome organization, basic biology, housekeeping genes and biochemical processes, as well as characteristic patterns of drug sensitivity and resistance that are similar to human-infecting species of Plasmodium . 22 23 Hence, P. berghei (NK-65) is the experimental model used for carrying out drug screening assays because P. falciparum cannot be maintained in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in ALP , bilirubin, SGOT and SGPT in malaria-infected individuals is an indication of liver dysfunction. Gorki et al [27, 28] reported elevated ALP, SGOT, SGPT and bilirubin levels in the infected control as compared to normal mice. The results of the present study are in agreement with these reports as significantly elevated ALP, SGOT, SGPT and bilirubin levels were observed in the infected control as compared to normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews addressed the anticancer activity of β-carboline derivatives and proposed different modes of action [ 9 , 15 , 17 ]. Similarly, the antimalarial activity of harmine and other β-carboline derivatives is also well-documented [ 18 , 19 , 20 ]. On the other hand, ferrocene is an important compound in bioinorganometallic chemistry due to its high stability, favorable redox properties, and low toxicity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%